Family Support for Lepers in Olu Village Lindu District Sigi Regency - Niswa Salamung; Chely Veronica Mauruh; Andi Nur Indah Sari; Fanny Metungku; Muliasi Muliasi (D'Nursing and Health Journal (DNHJ), 2021)
Introduction: Leprosy is a type of infectious disease that can cause very complex problems. From the results of interviews with health workers at the Pustu that people with leprosy take medicine at the Pustu every month. The results of observations at the Pustu on 2 leprosy sufferers, one of the patients accompanied by their family to go for treatment and take medicine at the Pustu and 1 patient came alone. The purpose of this study was to know the family support for leprosy sufferers in Olu Village, Lindu District, Sigi Regency. Method: This type of research is descriptive research. The population in this study were 30 people affected by leprosy in Olu Village. The sample in this study was that the entire population was used as a sample in Olu Village, amounting to 30 people. The sampling method was non-probability sampling with a total sampling approach model. Result: It shows that out of 30 respondents stated about family support for respondents, more families are supportive (53.3%) than those who are less supportive (46.7%), appreciation and information so that sufferers feel accepted in the midst of family and society and have a great desire for healing. Conclusion: More supportive than those who are less supportive. appreciation and information so that sufferers feel accepted in the midst of family and society and have a great desire for healing.